Signifikansi Perolehan Zakat Produktif: Pola Pengawasan Internal di Inisiatif Zakat Indonesia - Netta Agusti Agusti; Eko Wardoyo Wardoyo; Henderi Kusmidi (Saqifah: Jurnal Hukum Ekonomi Syariah, 2022)
This study discusses the implementation of supervision to maximize the acquisition of productive zakat funds at the Bengkulu Branch of the Inisiatif Zakat Indonesian. This research uses qualitative. Sources of data used are primary data and secondary data. Data collection techniques through observation, interviews, and documentation. To test the validity of the data, the researcher used triangulation analysis. The study's results found that the supervision of Productive Zakat at the Bengkulu Branch of the Inisiatif Zakat Indonesian began with tidying up the data and distributing the data to each member in the related field, each member giving a sign or schedule. To pay zakat, which is usually from donors. Some of this work is carried out manually and partly using an e-donation application. The best supervision rewards those who achieve their work targets and provides sanctions/reprimands for those who do not complete their work targets. The authors' findings support the findings of previous studies. Finally, this study recommends further discussing the control of productive zakat in the Indonesian zakat initiative.